Amylase enzyme production with variation of carbon sources and molecular identification of thermophilic fungus Aspergillus sp. LBKURCC304 from Bukik Gadang, West Sumatra, Indonesia - SARYONO SARYONO; SILVERA DEVI; TITANIA T. NUGROHO; WIDYLIA FITRI FADHILA; LORENA LORENITA; FIDA SELFIANA NASUTION; NABELLA SURAYA (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Saryono, Devi S, Nugroho TT, Fadhila WF, Lorenita L, Nasution FS, Suraya N. 2023. Amylase enzyme production with variation of carbon sources and molecular identification of thermophilic fungus Aspergillus sp. LBKURCC304 from Bukik Gadang, West Sumatra, Indonesia. Biodiversitas 24: 1200-1205. Amylase is an enzyme used to hydrolyze starch into smaller molecules. Starch degradation is very difficult because of the presence of 1-4 glucoside bonds from complex polysaccharides and the presence of enzyme accommodation centers, so the production of amylase is in great demand by industry. The production of amylase is strongly influenced by carbohydrates which act as inducers to stimulate the production of enzymes. This research was conducted to determine the effect of different carbohydrate sources on the production of amylase enzyme from thermophilic fungus Aspergillussp. LBKURCC304. Different carbon sources used werecassava, corn, taro, purple sweet potato, potato, breadfruit, canna, gembili, gadung, and sago. The effect of different carbohydrate sources on enzyme production was statistically tested using Duncan's Multiple Range Test (DMNRT) at a significant level of 5% and Principal Component Analysis (PCA). The results of molecular identification showed that carbohydrates from sago were a relatively better carbon source than other carbon sources, with an activity of 0.0391±0.0017 U/mL, anda specific activity of 0.0874±0.0049 U/mg. The highest (0.7651±0.0096 mg/mL) protein content wasrecorded from canna. Molecular identification showed that LBKURCC304 isolate was Aspergillus fumigatus.